2018
DOI: 10.32861/jssr.412.648.668
|View full text |Cite
|
Sign up to set email alerts
|

Research Trend in the Practice of Differentiated Instruction

Abstract: This article employed secondary data to critically examine policies, mission and vision of a private mission university in line with fundamental human rights and the safety of students. The high rate of violence and criminal activities across Nigeria seems to have given credence to such policies in as much as such policies emphasize students" safety and development. Therefore, academic freedom and students" fundamental human rights should be exercise within the policies designed to ensure students safety and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Additionally, there is a lack of studies conducted on participants from the young adult age group as demonstrated in the findings. Besides that, researchers can now be aware of how methodological variations can affect performance and in doing so re-evaluate or incorporate a more coherent and controlled approach such as eye-tracking (Hasrul, Hazita & Azizah, 2018;Sarah Yusri & Soh, 2019). Lastly, we have concluded the lack of studies done in Malaysia pens a huge gap in which more research can be done in order to fill in that gap.…”
Section: Resultsmentioning
confidence: 83%
“…Additionally, there is a lack of studies conducted on participants from the young adult age group as demonstrated in the findings. Besides that, researchers can now be aware of how methodological variations can affect performance and in doing so re-evaluate or incorporate a more coherent and controlled approach such as eye-tracking (Hasrul, Hazita & Azizah, 2018;Sarah Yusri & Soh, 2019). Lastly, we have concluded the lack of studies done in Malaysia pens a huge gap in which more research can be done in order to fill in that gap.…”
Section: Resultsmentioning
confidence: 83%
“…Bibliometric research related to DI has been conducted by scholars (AM et al, 2023;Dal & Abu, 2023;Kamarulzaman et al, 2018;Shareefa & Moosa, 2020;Sun & Xiao, 2021;Wei et al, 2022). Bibliometric research on existing DI certainly differs from this study.…”
Section: Introductionmentioning
confidence: 74%
“…The United States had the most research related to DI. Other research findings on bibliometric DI also stated that the USA had the most distribution of articles about the DI (AM et al, 2023;Dal & Abu, 2023;Kamarulzaman et al, 2018;Shareefa & Moosa, 2020;Sun & Xiao, 2021). The United States is the country that is most aggressively conducting differentiated learning because there is a policy that every school in the US must be able to show that children can use their minds well so that they are ready to be good citizens, ready to enter higher education, and also ready for productive jobs in the modern economy so that this is a challenge for every teacher and researcher to do learning with students who more diversity (Hogan, 2014).…”
Section: Discussionmentioning
confidence: 95%